Magnetic NiFe thin films composing MoS2 nanostructures for spintronic application - Yousef Vand, Mahdi; Jamilpanah, Loghman; Zare, Mohammad; Mohseni, Seyed Majid (Scientific reports, 2022)
We demonstrate a nanostructure layer made of Ni 80 Fe 20 (permalloy:Py) thin film conjugated MoS 2 nano-flakes. Layers are made based on a single-step co-deposition of Py and MoS 2 from a single solution where ionic Ni and Fe and MoS 2 flakes co-exist. Synthesized thin films with MoS 2 flakes show increasing coercivity and enhancement in magneto-optical Kerr effect. Ferromagnetic resonance linewidth as well as the damping parameter increaseed significantly compared to that of the Py layer due to the presence of MoS 2 . Raman spectroscopy and elemental mapping is used to show the quality of MoS 2 within the Py thin film. Our synthesis method promises new opportunities for electrochemical production of functional spintronic-based devices.